Economic Development and Democratization in China: A Perspective from Civil Political Participation - Zhang, Yang Wenxin; Jiang, Yanqing (Asian Development Policy Review, 2015)
Along with China?s economic development since the reform and opening up, political participation of Chinese citizens has increased a great deal in a variety of forms. Elections are becoming increasingly formal and substantial and the number of petitions is getting larger and larger, which are institutionalized forms of political participation. In the forms of non-institutionalized political participation, communications between the mass and public officials have increased significantly, and even the general mass can participate in government decision-making, changing their positions from a passive role to a relatively active one.